Analisis Kepuasan Konsumen terhadap Pelayanan Restoran Cepat Saji (Restoran X) dengan Metode Service Quality (Servqual) - Horax, Michelle; Sanjaya, Lucy (Metris: Jurnal Sains dan Teknologi, 2017)
RestaurantX is a fast food restaurant that emphasizes quality to obtain customer satisfaction. The process of fulfillment of consumer satisfaction, not only requires a quality product or service, but also requires a supportive service system. This study aims to analyze customer satisfaction ofRestaurantX service. The method used is Service Quality. This method measures the quality of service and be used to analyze the cause of a service problem. Dimensions used in this research are reliability, responsiveness, assurance, empathy, and tangible. Data collection techniques were conducted by distributing questionnaires to respondents. The result of the research using regression technique shows that the variables affecting customer satisfaction on RestaurantX service are clean environment both at the inside and the outside, lighting condition inside restaurant, list menu neatly and visibly clear by consumers, food portions served, and employees provide prompt and timely service. The result of the research by using Service Quality method states that RestaurantX service of employee responsive to consumer requirement and employees ability to respond consumer demand quickly need to improve due to big gap between expectation and consumer perception